Implementation of SBAR Communication For Nurse Handover in Nursing Services at Manimeri Health Center, Teluk Bintuni Regency - Dina Kristina Antoh; Blacius Dedi; Witri Hastuti (Jurnal Kesehatan dr. Soebandi, 2025)
Ineffective communication poses significant risks to patients, with 30% of nurses failing to provide accurate information to doctors, although 70% do provide good information, reducing patient risk (Depkes RI, 2008). Communication impacts both patients and healthcare workers, with nurses facing difficulties due to the lack of handover communication guidelines, which can endanger patients (Watulangkow et al., 2020). According to Permenkes No. 11 of 2017, 79.7% of incidents in Indonesian health centers result from ineffective communication. Dewi et al. (2019) found that the SBAR (Situation, Background, Assessment, Recommendation) technique in patient care reduces adverse events, near-miss incidents, potential injuries, no-harm incidents, and sentinel events. This study examines the impact of SBAR-based nurse handover on nursing service quality at Manimeri Health Center, Teluk Bintuni Regency, West Papua. Using a qualitative method with an exploratory phenomenological approach, the study involves seven participants. Data is analyzed using the Collaizi method, which offers clear, detailed steps. Findings reveal that SBAR-based nurse handover implementation in nursing services is suboptimal. Limited nurse understanding hinders the improvement and optimization of SBAR handover communication. Despite these challenges, there has been a notable change in the rate of adverse events following the research.